2017
DOI: 10.4172/2472-1654.100076
|View full text |Cite
|
Sign up to set email alerts
|

Patient Perceptions of the Caring Environment

Abstract: As technology at the point of care increases to ensure greater efficiency, effectiveness and patient safety, the impact of such technology needs to be explored for impact on patient perception of the caring environment. The evidence based practice pilot project based on the Iowa Model sought to answer if an ergonomic change in use surrounding technology improved patient perceptions of the caring environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…It has been observed that restricting misuse of antibiotics reduces resistance [9]. In 2017, WHO experts have revised the antibiotic section of EML (Essential Medicines List) where antibiotics are divided into three categories i.e.…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that restricting misuse of antibiotics reduces resistance [9]. In 2017, WHO experts have revised the antibiotic section of EML (Essential Medicines List) where antibiotics are divided into three categories i.e.…”
Section: Introductionmentioning
confidence: 99%